Tafakur Pandemi Covid-19 Perspektif Pendidikan Islam - Zuhby, Nawal El (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2021)
At the end of 2019 there were almost all countries affected by the covid-19 virus outbreak which caused a fairly high mortality rate. Coronaviruses (cov) causes the emergenceof more serious flu illnesses such as (MERS-CoV) and (SARS-CoV). This study aims to understand the notion of contemplation, the 19th plague, the understanding of Islamic education and how to contemplate in dealing with the covid-19 virus outbreak. Based on the background of the problem that examines how to meditate during the co-19 pandemic in the perspective of Islamic education, the researcher will provide a solution to the problem. Researchers use a qualitative research approach (qualitative research) and use the type of case studyresearch (casestudy).Becausethetypeof casestudy research itself is an inquiry activity that describes or explains what is happening in life and provides a way out for the problem under study. Meditate in dealing with the covid-19 virus outbreak in a way, always asking for protection fromAllahSWT,endeavor,trust, and believein the healingthatAllahSWT gave.